Three closely related (2E,200E)-3,300-(1,4-phenylene)- bis[1-(methoxyphenyl)prop-2-en-1-ones]: supramolecular assemblies in one dimension mediated by hydrogen bonding and C—Hp interactions - Aijia, Sim; Chidan Kumar, C. S.; Huey, Chong Kwong; Li, Yee Then; Win, Yip Foo; Ching, Kheng Quah; Naveen, S.; Chandraju, S.; Lokanath, N. K.; Warad, Ismail (International Union of Crystallography, 2017)
In the title compounds, (2E,20E)-3,30-(1,4-phenylene)bis[1-(2-methoxyphenyl)- prop-2-en-1-one], C26H22O4 (I), (2E,20E)-3,30-(1,4-phenylene)bis[1-(3-methoxyphenyl) prop-2-en-1-one], C26H22O4 (II) and (2E,20E)-3,30-(1,4-phenylene)bis[1- (3,4-dimethoxyphenyl)prop-2-en-1-one], C28H26O6 (III), the asymmetric unit consists of a half-molecule, completed by crystallographic inversion symmetry. The dihedral angles between the central and terminal benzene rings are 56.98 (8), 7.74 (7) and 7.73 (7) for (I), (II) and (III), respectively. In the crystal of (I), molecules are linked by pairs of C—H interactions into chains running parallel to [101]. The packing for (II) and (III), features inversion dimers linked by pairs of C—HO hydrogen bonds, forming R2 2(16) and R2 2(14) ring motifs, respectively, as parts of [201] and [101] chains, respectively.